Patient Safety and Medical Error Prevention in General Practice: A Comprehensive Systematic Review - Khard, Marwah Hussain Alawi; Tobiqe, Reem Fadhl; Barjas M, Aldawsari. Maha; Khardali, Amani Abdullah; khardali, Khulud Mohsen; Alirfan, Hamad Hussain; Alomari, Faisal Mohammed; Al mansour, Ali Saleh Mohammed; Hamad, Alyami Mohammed Yahya; Mansoor H, Al-Sadran, Ali (Journal of Ecohumanism, 2024)
Patient safety and medical error prevention remain critical issues in general practice, where medical errors can lead to adverse patient outcomes and increased healthcare costs. This systematic review synthesizes recent evidence on prevalent types of medical errors, effective prevention strategies, and outcomes of patient safety interventions within general practice settings. Following a comprehensive search across multiple databases, 52 studies published from 2014 to 2024 were included. Findings highlight medication errors, diagnostic inaccuracies, and communication lapses as the most common types of errors. Effective prevention strategies include the adoption of electronic health records (EHR), structured team communication protocols, checklist systems, and staff training programs on safety practices. These interventions have shown significant reductions in error rates and improvements in patient outcomes, though implementation is often hindered by barriers such as limited resources, resistance to change, and lack of training. This review underscores the importance of a multifaceted approach that combines technological, organizational, and educational interventions to enhance patient safety in general practice. Future research should explore long-term impacts of these interventions and address context-specific challenges to foster a culture of safety in healthcare settings.